Impact of Incentives and Work Discipline on Employee Performance - Damo, Gilbert Alexander; Rasyid, Abdul; Ameliana, Yana (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the simultaneous influence of incentives and work discipline on employee performance at PT BFI Finance Jayapura Branch. The hypothesis is that increasing incentives and work discipline will enhance employee performance. Research Design and Methodology: The research design uses a quantitative survey method. Data was collected through questionnaires distributed to 40 PT BFI Finance Jayapura Branch employees. Variables studied include incentives, work discipline, and employee performance. Data analysis was conducted using multiple linear regression to test the simultaneous effects of the independent variables on the dependent variable. Findings and Discussion: The findings indicate that incentives and work discipline significantly influence employee performance. The analysis shows that simultaneous incentives and work discipline increases contribute to improved employee performance. This study supports motivation theories such as Vroom's Expectancy Theory and Herzberg's Two-Factor Theory, emphasizing the importance of incentives and discipline in enhancing performance. Implications: The implications suggest that PT BFI Finance management should develop comprehensive incentive programs and effective work discipline strategies to boost employee performance. The study also recommends further research to explore the long-term effects of incentives and work discipline, considering additional variables such as leadership and organizational culture.